1993
DOI: 10.1203/00006450-199307000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Carotid, Not Aortic, Chemoreceptors Mediate the Fetal Cardiovascular Response to Acute Hypoxemia in Lambs

Abstract: ABSTRACI'. The fetal cardiovascular response to acute hypoxemia consists of a decrease in heart rate, a variable change in mean arterial pressure, and an increase in peripheral vascular resistance. This response is mediated by the arterial chemoreceptors. To determine whether chemoreceptors in the carotid artery or in the aorta mediate the fetal cardiovascular response to acute hypoxemia, we studied the response to acute hypoxemia in fetal lambs at 125 to 130 d of gestation after selective carotid (six fetuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 5 publications
8
67
0
5
Order By: Relevance
“…During the first minute of occlusion the expected bradycardic response was present in both groups and no differences in the magnitude of the fall in heart rate were observed. This initial bradycardia is thought to represent a chemoreceptor response that is vagally mediated (Bartelds et al, 1993). Consistent with our data, in chronically hypoxic high altitude-exposed fetal sheep with a comparable reduction in fetal arterial pO 2 and without acidosis, the bradycardic response to umbilical cord occlusion was shown not to be affected (Imamura et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…During the first minute of occlusion the expected bradycardic response was present in both groups and no differences in the magnitude of the fall in heart rate were observed. This initial bradycardia is thought to represent a chemoreceptor response that is vagally mediated (Bartelds et al, 1993). Consistent with our data, in chronically hypoxic high altitude-exposed fetal sheep with a comparable reduction in fetal arterial pO 2 and without acidosis, the bradycardic response to umbilical cord occlusion was shown not to be affected (Imamura et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism of this late fall is less clear. Among the possible mechanisms are recruitment of other peripheral chemoreceptor input (Bartelds et al, 1993), a synergistic effect of severe hypercarbia on carotid chemoreceptors (Blanco et al, 1984), a direct effect of ischemia on cardiac pacemaker cells (Gryshchenko et al, 2002), and an activation of the cardioinhibitory Bezold-Jarisch reflex (Aviado and Guevara, 2001;Dawes and Comroe, Jr., 1954). This latter reflex originates from the stimulation of both mechanically and chemically sensitive receptors in the ventricle which can be elicited by coronary ischemia and asphyxia (Thoren, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems likely that chemo-rather than baroreceptors mediate the rapid RBF responses and bradycardia during hypoxia, since the rise in MAP was slow in the CSD group and did not reach significance in the intact group. Previous studies have demonstrated that the initial bradycardia during hypoxia is a carotid rather than an aortic chemoreflex response (Bartelds et al 1993;Giussani et al 1993). In accordance with these findings we have shown a striking effect of CSD on bradycardia, as well as on the initial fall in RBF, during hypoxia.…”
Section: Blood Gases and Phsupporting
confidence: 91%
“…There is abundant evidence that fetal hypoxia causes bradycardia, primarily through a carotid chemoreceptor reflex (15)(16)(17). Accordingly, carotid arterial hypoxia may contribute to PCI-related FHI.…”
Section: Discussionmentioning
confidence: 99%